2016
DOI: 10.1063/1.4955410
|View full text |Cite
|
Sign up to set email alerts
|

GHz spurious mode free AlN lamb wave resonator with high figure of merit using one dimensional phononic crystal tethers

Abstract: This letter reports a spurious mode free GHz aluminum nitride (AlN) lamb wave resonator (LWR) towards high figure of merit (FOM). One dimensional gourd-shape phononic crystal (PnC) tether with large phononic bandgaps is employed to reduce the acoustic energy dissipation into the substrate. The periodic PnC tethers are based on a 1 µm-thick AlN layer with 0.26 µm-thick Mo layer on top. A clean spectrum over a wide frequency range is obtained from the measurement, which indicates a wide-band suppression of spuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…To obtain the wide band gap, a lot of PnC structures have been designed [17,18,19,20,21,22,23,24,25], and applied to resonators of different shapes [18,19,20,22]. Phononic crystal can reduce the energy dissipated through anchors.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the wide band gap, a lot of PnC structures have been designed [17,18,19,20,21,22,23,24,25], and applied to resonators of different shapes [18,19,20,22]. Phononic crystal can reduce the energy dissipated through anchors.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have studied the defect states in such phononic crystals and demonstrated their usefulness as waveguides, filters, and cavity modes. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] In a recent paper, 37 we have proposed a phononic crystal based on 1D grooves placed periodically in one direction and surmounted by disc shaped thin metallic films deposited periodically on each groove. This platform enabled us to obtain highly confined disc shaped radial contour modes, characterized by their high Q factor and surface mode nature.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach has been to etch acoustic reflectors into the anchoring boundaries of the resonator to reflect the outgoing acoustic waves from the supports back into the resonator [ 5 ]. Moreover, phononic crystals (PnCs) have been hybridized with Silicon (Si) [ 6 ], Aluminum Nitride (AlN) [ 7 , 8 ], AlN-on-Si [ 9 , 10 , 11 , 12 ] and Gallium Nitride (GaN) [ 13 ] resonators with either one-dimensional (1D) or two-dimensional (2D) periodicity. PnCs are inhomogeneous periodic structures (e.g., solid–air) that shape the transmission of phonons through the PnC.…”
Section: Introductionmentioning
confidence: 99%
“…However, cavity resonators and waveguides are associated with lower Qs and higher insertion losses. Alternatively, PnC based supporting tethers [ 6 , 7 , 8 , 9 , 10 , 11 ] have been used in lieu of simple beam tethers in resonators to reduce anchor loss and thus enhancing Q. As propagation of acoustic waves at frequencies within the ABG is prohibited within the PnC [ 23 ], placing PnCs close to the resonator where acoustic waves are expected propagate out has the benefit of reducing anchor loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation